Lista nominal de especies de ciempies (chilopoda) para México - Cupul Magaña, Fabio Germán (BIOCYT Biología Ciencia y Tecnología, 2010)
After the revision of the on-line electronic database of the centipedes (Chilopoda) of the world, Chilobase, the first complete list of species from Mexico was generated. A total of 175 species was cited from the country and these species represent 5.5% of the world total diversity.